Anti-inflammatory effects of tick salivary protease inhibitors on mouse microglial cells - Mayr, Yifan (Jihočeská univerzita, 2017)
This project evaluated the effect of several tick salivary protease inhibitors on inflammation induced in BV-2 microglial cells, by assessing levels of inflammation mediators and cell adhesion.
Anti-inflammatory effects of tick salivary protease inhibitors on mouse microglial cells